2020
DOI: 10.1038/s41596-020-0327-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of task-based functional MRI data preprocessed with fMRIPrep

Abstract: Functional magnetic resonance imaging (fMRI) is a standard tool to investigate the neural correlates of cognition. fMRI noninvasively measures brain activity, allowing identification of patterns evoked by tasks performed during scanning. Despite the long history of this technique, the idiosyncrasies of each dataset have led to the use of ad-hoc preprocessing protocols customized for nearly every different study. This approach is time-consuming, error-prone, and unsuitable for combining datasets from many sourc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(72 citation statements)
references
References 56 publications
0
64
0
Order By: Relevance
“…Results included in this manuscript come from preprocessing performed using Fmriprep version 1.4.1 (RRID:SCR_016216) 42 , 43 , a Nipype based tool (RRID:SCR_002502) 44 , 45 . Each T1w (T1-weighted) volume was corrected for INU (intensity non-uniformity) using N4BiasFieldCorrection v2.1.0 46 and skull-stripped using antsBrainExtraction.sh v2.1.0 (using the OASIS template).…”
Section: Methodsmentioning
confidence: 99%
“…Results included in this manuscript come from preprocessing performed using Fmriprep version 1.4.1 (RRID:SCR_016216) 42 , 43 , a Nipype based tool (RRID:SCR_002502) 44 , 45 . Each T1w (T1-weighted) volume was corrected for INU (intensity non-uniformity) using N4BiasFieldCorrection v2.1.0 46 and skull-stripped using antsBrainExtraction.sh v2.1.0 (using the OASIS template).…”
Section: Methodsmentioning
confidence: 99%
“…As such, we found that surface-based alignment, combined with the cortical parcellation approach, exhibited significant benefits in statistical sensitivity to task effects relative to more standard volume-based alignment approaches; consequently, the data and analyses reported here utilize this approach. Additionally, we are now in the process of shifting our preprocessing pipeline to fMRIprep (Esteban et al, 2018(Esteban et al, , 2020, as we have that it yields further benefits in terms of standardization, QA/QC, and statistical sensitivity, relative to the HCP pipelines (Etzel et al, 2019). Most recently, we have explored a second stage pre-processing approach using a whole-brain neural model derived from resting-state fMRI scans to filter out intrinsic activity dynamics and provide even greater sensitivity and temporal precision regarding event-related activity dynamics (Wang et al, 2020).…”
Section: Analysis Workflowmentioning
confidence: 99%
“…Preprocessing was performed using fMRIPrep 1.4.0 (Esteban, Ciric, et al, 2019; Esteban et al, 2018) RRID:SCR_016216), which is based on Nipype 1.2.0 (Esteban, Markiewicz, et al, 2019); RRID:SCR_002502).…”
Section: Methodsmentioning
confidence: 99%